ANALISIS YURIDIS PENERAPAN SANKSI TILANG TERHADAP PEMILIK KENDARAAN YANG TIDAK MEMBAYAR PAJAK TAHUNAN KENDARAAN BERMOTOR - Feryandi, Feryandi; Ukas, Uk (LPPM Universitas Putera Batam, 2019)
The application of ticket sanctions to traffic violations is indeed necessary to maintain security conduciveness in traffic. In Law Number 22 Year 2009 no specific sanctions are given if the annual tax display is not carried out. The ticket penalties given by Traffic Police have burdened the community because besides these sanctions it is not relevant in the case of motorized vehicles that do not pay annual taxes. As for the formulation of the problem in this study is how the implementation of ticketing sanctions on vehicle owners who do not pay annual motor vehicle taxation and the obstacles posed to the application of ticket penalties for vehicle owners who do not pay annual taxes on motorized vehicles. The aim of this research is to knowing the application of ticketing sanctions to vehicle owners who do not pay annual motor vehicle taxation and to find out the obstacles posed by the application of ticket penalties for vehicle owners who do not pay annual taxes on motorized vehicles. The type of research is normative legal research, namely the method or method used in legal research conducted by examining existing library materials. Giving sanctions by traffic police to vehicle owners who do not pay annual taxes on motorized vehicles not justified by law so that it cannot be applied. There are several factors that result in not being able to cross the ticket penalty, including legal factors, law enforcement factors, community factors.